2006
DOI: 10.1111/j.1469-0691.2006.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ica operon carriage and biofilm production in Staphylococcus epidermidis isolates causing bacteraemia in bone marrow transplant recipients

Abstract: The clinical significance of coagulase-negative staphylococci isolated from blood culture is typically assessed on the basis of a combination of clinical and microbiological criteria. However, these criteria are difficult to apply to haematology patients who are highly immunosuppressed and from whom blood cultures are obtained most frequently through a central venous catheter. This study analysed 112 episodes of Staphylococcus epidermidis bacteraemia that occurred in 79 bone marrow transplant recipients. In 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
(52 reference statements)
4
16
1
Order By: Relevance
“…Partial sequencing of atlE confirm the existence of two major lineages among S. epidermidis strains (30), as previously found by pulsed-field gel electrophoresis analysis of isolates from Brazil (21), Italy (5), Sweden (23), and France (20). During preliminary comparisons of PJI and control strains, we felt that allele 1 (i.e., the type strain sequence) was a potential marker of infectious strains.…”
supporting
confidence: 81%
“…Partial sequencing of atlE confirm the existence of two major lineages among S. epidermidis strains (30), as previously found by pulsed-field gel electrophoresis analysis of isolates from Brazil (21), Italy (5), Sweden (23), and France (20). During preliminary comparisons of PJI and control strains, we felt that allele 1 (i.e., the type strain sequence) was a potential marker of infectious strains.…”
supporting
confidence: 81%
“…The ica locus and biofilm formation are important parameters for staphylococcal colonisation and survival on IMDs (Fluckiger et al 2005); however, recent publications have revealed the emergence of biofilm-positive and ica-negative staphylococcal clinical isolates (Qin et al 2007). Recently, Ninin et al (2006) observed an increase in the subpopulation of biofilm-positive, intercellular adhesin (ica)-negative S. epidermidis isolates to 9.17% of the total 109 clinical isolates that caused bacteraemia in bone-marrow transplant recipients. Chokr et al (2006) also noted that PIA synthesis alone is not sufficient to produce a biofilm and that staphylococci can form a biofilm independent of PIA production, which was consistent with the findings that the presence of the ica locus alone is not sufficient for biofilm formation (Fitzpatrick et al 2002).…”
Section: Polysaccharide Intercellular Adhesin (Pia)mentioning
confidence: 99%
“…In contrast, S. aureus strains lacking the ica locus appear to colonize to the same extent as the wild type (WT) in animal models of implant infections (16,21,23,36), although Fluckiger et al did show a defect in growth for the ica mutant in an implant infection model when competed against the WT (21). Also, several recent studies have shown that the presence of icaA was not predictive of pathogenicity among staphylococci (4,24,42,52,59). In contrast, a clear role for the ica locus has been demonstrated in biofilm formation and infection models for Staphylococcus epidermidis (6,42,53,70).…”
mentioning
confidence: 99%